(3OQGSI JMdjdjIs - (3djK YHO GdGejQ(B, (3GdUjGZs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3JHGOd GdNHQGJ h GdJYGhf Hjf GdOhd GdYQHjI , GJaGbjI GdJLGQI GdYGdejI h CKQgG Ydi Shb GdJGejf aj GdOhd GdYQHjI , eHGOF MhceI GdTQcGJ h JWHjbGJgG aj TQcGJ GdJCejf , XGgQI MQb GdGSYGQ , fTQ GdKbGaI GdbGfhfjI , JShjb GdefJL GdJCejfj , OhQ TQcGJ GdhSGWI GdYQHjI aj GdaJQI GdbGOeI , JGejf GdeQcHGJ aj GdhWf GdYQHjs
Keywords: (3GdCShGb GdYQHjIs; (3GdJCejf (B- (3GdHfhcs; (3GdJLGQI GdOhdjIs